2020
DOI: 10.1111/ajae.12112
|View full text |Cite
|
Sign up to set email alerts
|

Technology and Technical Efficiency Change: Evidence from a Difference in Differences Selectivity Corrected Stochastic Production Frontier Model

Abstract: This study presents a new approach to evaluate the economic impact of development projects for cases where baseline and endline data for comparable treated and control samples are available. An important contribution is to bring together propensity score matching (PSM) and difference-indifferences (DID) techniques, commonly used in impact evaluation studies, with stochastic production frontiers (SPF) that have become well-established in the productivity literature. To illustrate our proposed framework, we use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…Further, as PwD agreed to use a technological device as part of the intervention, it may be that participating PwD were of greater health compared to a general sample of PwD. The self-selection bias is a known problem in research [ 63 ]. For example, Keiding & Louis (2016) argue that self-selection directly affects the validity of cross-sectional analyses and longitudinal trends [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, as PwD agreed to use a technological device as part of the intervention, it may be that participating PwD were of greater health compared to a general sample of PwD. The self-selection bias is a known problem in research [ 63 ]. For example, Keiding & Louis (2016) argue that self-selection directly affects the validity of cross-sectional analyses and longitudinal trends [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, TE scores can be estimated following the standard SPF models. The full detailed model and its estimation steps are referred to (Bravo-Ureta et al, 2020;Bravo-Ureta et al, 2012;Greene, 2010).…”
Section: Jadee 112mentioning
confidence: 99%
“…The unmatched and matched results from SPF are in Tables 6 and 7, respectively. This study reported t-statistics instead of standard errors because t-statistics are determined by the coefficient of each variable and its corresponding standard error, following some previous studies [12,28,29]. The pooled results are calculated using Equation (2).…”
Section: Stochastic Production Frontier (Spf)mentioning
confidence: 99%